PELATIHAN PIJAT OKETANI UNTUK MELANCARKAN ASI IBU MENYUSUI PADA KADER KESEHATAN - Ellyzabeth Sukmawati; Dahlia Arief Rantauni; Yuli Sya’Baniah Khomsah; Umi Fatonah; Nurhasanah Nurhasanah (Jurnal Abdimas Bina Bangsa, 2023)
Oketani Massage is a complementary therapy with breast care methods to increase breast milk production. The solution offered for this problem is by providing health cadre training on Oketani massage as a companion of exclusive breastfeeding. The method of implementing this service was carried out by providing training through discussion and QnA to the participants using lectures method with the help of powerpoint media, mannequins, and videos. The place for the dedication program was carried out in Kalikudi Village, Maos District, Cilacap Regency with a total of 51 health cadre participants with an allocation time from December 2022 to February 2023. Oketani massage is a solution/alternative for breastfeeding mothers to expedite the process of breastfeeding the baby. Through an increase in the knowledge of Posyandu cadres about this Oketani massage, it is expected that the cadres can spread it to the community. This is one of the advantages of community service activities